Dependences of Confining Size and Interfacial Curvature on the Glass Transition of Polydimethylsiloxane in Self‐Assembled Block Copolymers. Issue 3 (22nd January 2018) - Huang, Zijie; Jiang, Jing; Shi, Lingying; Wang, Xiaoliang; Xue, Gi; Li, Linling; Shen, Zhihao; Zhou, Dongshan
Abstract: Lamellae (LAM), hexagonally packed cylinders (HEX), and double gyroid (GYR) phases of diblock copolymer polydimethylsiloxane‐ b ‐poly‐2, 5‐bis(4‐methoxyphenyl)‐oxycarbonyl styrene (PDMS‐ b ‐PMPCS) can be obtained by controlling PMPCS length and thermal annealing conditions. This provides a system to study the glass transition of polymers under the well‐defined confining geometries and interfacial physicochemical properties. By taking advantage of ultrafast differential scanning calorimeter, the glass transition temperature ( T g ) of PDMS in the confined state is measured without destroying the nanophase structure sustained by the rigid PMPCS domains. Depending on the detailed confining geometry, the T g and T g breadth of PDMS show a clear difference by alternating the nanostructure and confining size. When annealing at higher temperatures, the decreases of T g and T g breadth with increasing confining size are observed, which are due to the subtle thermal expansion of block copolymer. Besides, the interfacial curvature effect on the T g of PDMS is emphasized: the confining size dependence on T g of PDMS block gradually becomes stronger as the interfacial curvature changes from negative (in GYR), to zero (in LAM) and to positive (in HEX). Such results explicitly elaborate the glass transition behavior of PDMS confined in block copolymer with various nanophase structures. Abstract : The glass transition temperatures ( T g ) of three kinds of polydimethylsiloxane (PDMS) nanodomains (lamellae, hexagonal, and gyroid geometries) in self‐assembled block copolymer (PDMS‐b‐PMPCS) are investigated, which not only display an obvious confining size dependence, but also a striking interfacial curvature effect.